RELIABILITY ANALYSIS OF FIXED PROCESSING PLATFORM DUE TO SEABED SUBSIDENCE AND THE EFFECT OF WAVE LOAD IN DECK - Cendekia Suprobo, Linda
The structural integrity of fixed platform may be affected from excessive load on structure and insufficient strength of the structure. Another factor which affects the structural integrity is seabed subsidence. Seabed subsidence occurs due to vertical movement of soil layers and soil consolidation. The impact of seabed subsidence will lead to decreased of deck clearance or air gap and cause wave hits the deck. The aim of the study is to determine the effect of wave load in deck by pushover and reliability analysis. The pushover analysis is performed first by considering 100- year environmental load to obtain RSR. The wave height at the collapse is calculated based on RSR. The wave load in deck calculation is according to American Petroleum Institute (API). The pushover with inclusion wave load in deck is necessary to be carried out to gain the updated RSR. The reliability analysis is computed by involving base shear of fixed platform at the collapse from pushover analysis with wave load in deck. FORM and Monte Carlo simulation technique method are adopted in the analysis. One million data of wave height and wave period as random variables is generated by MATLAB software. This study is also to perform the probability of failure and reliability index due to wave load in deck. As expected, the updated RSR with wave load in deck is lower than the RSR without wave load in deck. Then, the probability of failure increases with the increase of the depth of subsidence. Therefore, the reliability index decreases with the increase of the depth of subsidence.